Taṣmīmu al-Wasāil al-Taʻlīmiyyah bi Barnāmiji Makru Media Flash fi al-Tadrībāt al-Qawāʻid Muassasan ʻalā Tahlīli al-Akhṭaʻ fi al-Mādati al-Taʻbīr al-Tahrīrī - Anailil Fasikhah; Mispani Mispani; Abd Rahman Abd Gaffar; Muhamad Agus Mushodiq (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2023)
Darussalam Gontor Modern Boarding School is one of the Islamic boarding schools that pays great attention to teaching Arabic. In making ta'bir ‘essay’ there are still many errors in the structure and teachers have tried to overcome the errors contained in their writings so that researchers see the need for media development with the use of modern technology. The purpose of this study is to develop learning media using macro flash which contains exercises on rules based on errors in al-Taʻbīr al-Tahrīrī lesson and to see the effectiveness of using macromedia flash in Darussalam Gontor Modern Boarding School. The type of research used is Research and Development (R&D), using qualitative-quantitative research methods, to calculate researcher data using the SPSS 16 program. From the results of the study, researchers concluded that the media product developed was in the form of the first, front screen which is the title of the program and contains a program start button. Second, the screen contains general buttons consisting of muqadimah, learning objectives, things that must be considered by the teacher and buttons to go to the practice screen. Third, the screen contains a button to go to each training title that will be done. Fourth, a screen containing exercises. The effectiveness of the program can be seen from the pre-test and post-test scores in small groups and large groups as well as from the answers to student questionnaires that show that the Macromedia flash program helps teachers and students in increasing their abilities in qāidah naḥwiyah ‘Arabic structure’. After going through several stages, researchers hope that there will be further researchers who will develop technology-based learning media in other subjects.